Superstrings and other things : a guide to physics - Calle, Carlos I. (Boca Raton : CRC Press, 2020)
"Continuing to take readers on a uniquely accessible journey through physics, Superstrings and Other Things, Third Edition, explains the basic concepts of motion, energy, and gravity, right up to the latest theories about the structure of matter, the origin and structure of the universe, and the beginning of time. Fully updated throughout, the book explores major historical discoveries and the scientists behind them. In addition, this comprehensive text details the breath-taking frontiers of physics being explored today. Offering non-science students access to the highest peaks of physics, Dr. Calle translates concepts so they can be appreciated by those with willing curiosity and imagination. Features Provides up-to-date coverage of modern physics Offers non-science students and laymen access to the highest peaks of physics Showcases modern applications of physics in our everyday world"--
OCLC-licensed vendor bibliographic record.
Keywords: Physics; Physical scientists; Discoveries in science; SCIENCE / Astrophysics & Space Science; SCIENCE / Physics